2006
DOI: 10.1002/mawe.200500005
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Behavior of Sn-Ag Alloys in Sodium Fluoride Solutions

Abstract: Passivation and corrosion behavior on Ag, Sn and Sn-Ag alloys were studied using various electrochemical techniques, i.e. opencircuit, potentiodynamic polarization and impedance measurements. The specimens were polarized between -1000 and 500 mV vs. saturated calomel electrode (SCE) in naturally oxygenated NaF solution of different concentrations. The results of potentiodynamic polarization showed that each of i corr and i c increases with increasing either Sn% or F -concentration. EIS measurements under open … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…The n value was found equal to 0.613, 0.311, 0.616, 0.498, 0.368, and 0.368 for samples I-VI, respectively. The results reveal that alloy II has the lowest corrosion rate among the studied six samples, in agreement with the open circuit results and those reported previously on the same samples [14,18], where the corrosion vulnerability increases in the sequence II (low) < V < IV, VI < I, III (high). It seems that an important factor which control the corrosion behavior of Sn-Ag alloy is its solid phase composition, hence the intermetallic phase 26Sn-Ag (sample II) as well as the eutectic phase 96.5Sn-Ag (sample V) are the two compositions exhibiting better anti-corrosion properties.…”
Section: Effect Of Concentrationsupporting
confidence: 82%
See 2 more Smart Citations
“…The n value was found equal to 0.613, 0.311, 0.616, 0.498, 0.368, and 0.368 for samples I-VI, respectively. The results reveal that alloy II has the lowest corrosion rate among the studied six samples, in agreement with the open circuit results and those reported previously on the same samples [14,18], where the corrosion vulnerability increases in the sequence II (low) < V < IV, VI < I, III (high). It seems that an important factor which control the corrosion behavior of Sn-Ag alloy is its solid phase composition, hence the intermetallic phase 26Sn-Ag (sample II) as well as the eutectic phase 96.5Sn-Ag (sample V) are the two compositions exhibiting better anti-corrosion properties.…”
Section: Effect Of Concentrationsupporting
confidence: 82%
“…On examining the data, it seems that the total resistance (R T ) value, which determines the resistive property of the oxide layer, is a suitable indicative parameter for explaining the role of the solid phase composition on the passive film behavior of Sn-Ag alloys at different sulfate concentrations. Also, the reciprocal capacitance of the passive film (1/C) is directly proportional to its thickness [14,24]. As indicated by the results of Table 3 and Fig.…”
Section: Electrochemical Impedance Measurementssupporting
confidence: 51%
See 1 more Smart Citation
“…Both the cathodic and anodic curves exhibit Tafel behavior. These results enable the determination of various electrochemical corrosion parameters of the two electrodes using Thales software for i/E analysis [20][21][22].…”
Section: Potentiodynamic Polarization Measurementsmentioning
confidence: 99%
“…Duckett et al [5] observed that addition of tin metal to silver metal increased progressively the hardness and tensile strength of silver. In an earlier article [6,7] , the electrochemical behavior of four Sn-Ag alloy samples was investigated in NaF and NaOH solutions and the results were compared with the behavior of their pure metals tin and silver.…”
Section: Introductionmentioning
confidence: 99%